The quality of health parasocial opinion leaders on social media. A literature review - Chew, Saw Teck; Emma Mohamad,; Sabariah Mohamed Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The growing popularity of social media usage has led to growing social media revolution capable of replacing traditional communication media. This landscape change not only helps individuals in communicating, searching for health information and thus sharing information on social media, but also promoting changes in the types and functions of health opinion leaders. Social media opinion leaders have more autonomy in determining content agenda and direction that they intend to convey to and share with their followers. Individuals now make decisions on health issues without relying entirely on the advice of doctors or professional bodies as they are also persuaded and influenced by the parties they deem trustworthy, including opinion leaders. Therefore, it is important for us to understand the process that these opinion leaders go through in creating health messages on social media and the quality of relationship they have with their followers. This paper will discuss past literature and research on the model of parasocial opinion leadership between health opinion leaders and their followers who use social media to communicate and consult on health issues and messages in the relationship process as well as to examine the issues and circumstances of health opinion leaders that exist on social media from the health perspective. 10 out of 545 articles have been identified for analytical purposes in tandem with the observed theme. The analyses of the studies illustrate a situation in which the characteristics of opinion leaders may influence the attitude and behaviour of the audience in health context. However, studies on the functions of health opinion leaders in social media are still lacking.